Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1039/b100435m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of brookite TiO2 nanoparticles by thermolysis of TiCl4 in strongly acidic aqueous media

Abstract: Nanometric particles of titania, brookite and rutile polymorphs were synthesised by thermolysis of TiCl 4 in concentrated HCl solutions. The Cl : Ti molar ratio seems to be the key factor in determining the crystalline phases and their relative proportions as well as the particle size and a large proportion of brookite can be obtained under specific conditions. The complex Ti(OH) 2 (Cl) 2 (OH 2 ) 2 seems to be the precursor of the brookite phase. The presence of chloride ions is also necessary to stabilise bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
271
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(304 citation statements)
references
References 24 publications
20
271
1
1
Order By: Relevance
“…[66][67][68][69][70][71][72][73] Much less is known about the ternary Ti-Fe-O diagram when dealing with nanoparticle synthesis in water. [74][75][76] In the 2-6 pH range, both metal ions first form an amorphous or very poorly organized hydroxide precipitate.…”
Section: Nanoparticle Characterizationsmentioning
confidence: 99%
“…[66][67][68][69][70][71][72][73] Much less is known about the ternary Ti-Fe-O diagram when dealing with nanoparticle synthesis in water. [74][75][76] In the 2-6 pH range, both metal ions first form an amorphous or very poorly organized hydroxide precipitate.…”
Section: Nanoparticle Characterizationsmentioning
confidence: 99%
“…Besides, the pure anatase phase suggests negligible effect of Cl -, NO 3 -and ClO 4 -anions on the TiO 2 phase formation even though these species are known to stabilize rutile and brookite. [16][17][18] The SAXRD of TiO 2 and TiO 2 HA1M ( Figure 1B) shows a broad intense peak centered at 1.5°. Although the Bragg reflections of the space group are not resolved, the presence of a low angle diffraction peak suggests that the samples possess a semi-organized mesoporous structure with relative uniform pores, but without long range ordering.…”
Section: Resultsmentioning
confidence: 99%
“…Our study demonstrated that the desired crystalline structure and morphology can be controlled at the molecular level by selection of a compound with an appropriate coordination architecture. Journal of the Ceramic Society of Japan 119 [6] 513-516 2011…”
Section: Discussionmentioning
confidence: 99%